PCB contamination in marine sediments from Golfo Dulce, Pacific coast of Costa Rica - Spongberg, Alison L. (Revista de Biología Tropical, 2004)
Twenty-nine marine sediment samples collected from 1996 through 2002 from the Golfo Dulce embayment of Costa Rica were analyzed for PCB concentrations. The Esquinas River and Rincon Bay in the northern and western part of the gulf had relatively low overall concentrations of PCBs, with no samples having greater than 2.1 µg/g dw sediment. The Port of Golfito had the highest overall concentrations, ranging up to 15.7 µg/g dw sediment. These samples were also dominated by higher chlorinated congeners. Samples from the deeper (>100m) waters in the northern part of the gulf, as well as within the sediment plume from the Rio Coto Colorado had intermediate values. Within the Rio Coto Colorado sediment plume the concentrations did decrease with increasing depth and the congeners showed a shift towards less chlorinated congeners with depth. However, the deep northern basin had some of the highest PCB concentrations and the shift towards less chlorinated congeners was not apparent or significant. Whether the anoxic conditions that exist in the deep waters are capable of initiating dechlorination is still unknown. Overall, the data from Golfo Dulce show moderate PCB contamination, despite the pristine nature of the gulf and surrounding lands.